2012
DOI: 10.1179/1362171811y.0000000074
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of friction stir welded 7042-T6 extrusions through differential scanning calorimetry

Abstract: Extruded and T6 tempered plates of 7042, an Sc modified Al-Zn-Mg-Cu alloy, were joined by friction stir welding (FSW) at a constant weld velocity and various pin rotation speeds (PRSs). At a low PRS, hardness decreased from each edge of the weld to a local minimum at the weld centre, but at a high PRS, the hardness initially decreased from each edge of the weld, but then rose towards the weld centre. The transition in the hardness profile was related to different heating and cooling conditions during FSW. Diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…UTS, YS, and E were reported to increase with the increase in the revolutionary pitch and then decrease after a certain value of the same. Similar reporting on the variation of weld quality in FSW process can be found in the related works by different researchers (Li and Liu 2013;Lim et al 2004;D'Urso et al 2009;Kamp et al 2009;Buffa et al 2013;Hamilton et al 2012;Miyazawa et al 2012). Researchers have presented the effect of various process parameters over the quality of the weld, but none has reported on the inconsistency of the weld quality over the same range of process parameters.…”
Section: Introductionmentioning
confidence: 57%
“…UTS, YS, and E were reported to increase with the increase in the revolutionary pitch and then decrease after a certain value of the same. Similar reporting on the variation of weld quality in FSW process can be found in the related works by different researchers (Li and Liu 2013;Lim et al 2004;D'Urso et al 2009;Kamp et al 2009;Buffa et al 2013;Hamilton et al 2012;Miyazawa et al 2012). Researchers have presented the effect of various process parameters over the quality of the weld, but none has reported on the inconsistency of the weld quality over the same range of process parameters.…”
Section: Introductionmentioning
confidence: 57%
“…Transformation Temperatures Estimated (From DSC Data) for Different Weld Conditions at the Weld Edge (Retreating Side) and Weld Center. [28] Welding Condition (rev min Figure 7a presents the material flow behavior of surface material tracers during the 250 rev min À1 condition with color shading indicating the temperature history. As seen in the figure, surface tracers under the shoulder and near the weld edge can reach temperatures of 618 K (345 °C), temperatures just greater than or approximately equal to the weld edge exothermic reaction temperature [604 K (331 °C)] for this weld condition.…”
Section: Table III Endothermic and Exothermic Peakmentioning
confidence: 99%
“…This flow of material effectively raises the advancing side temperature above that of the retreating side. In a separate study of friction stir welded 7042-T6, Hamilton et al [28] noted that tensile samples extracted from the welded plates fractured toward the advancing side, suggesting that the advancing side was softer than both the weld center and retreating side. Through DSC analysis of samples taken from the weld, they hypothesized that the advancing side temperature reaches an endothermic transformation temperature before the retreating side, i.e., the advancing side is hotter, and becomes depleted in strengthening precipitates.…”
Section: A Materials Flow and Temperature Distributionmentioning
confidence: 99%
“…In their differential thermal analysis through DSC, Hamilton et al [28] demonstrated that three phase transformations occur in the 7042-T6 alloy during heating at 10 K/min between room temperature and 673 K (400°C). These are (i) an endothermic transformation occurring near 438 K (165°C) and caused by the dissolution of the non-equilibrium GP zones and g¢ particles, (ii) an exothermic transformation occurring near 489 K (216°C) and caused by the formation and growth of the equilibrium g and/or T phases, and (iii) an endothermic transformation occurring above~523 K (250°C) due to dissolution of these equilibrium phases.…”
Section: B Formation Of Onion Ringsmentioning
confidence: 99%
See 1 more Smart Citation